The Effective Lower Bound for the Policy Rate in Euroized Economies-An Application to the Case of Albania - della Valle, Guido (IMF Working Papers; Working Paper ;, 2018)
Based on the experience of the Bank of Albania, the paper proposes a framework to estimate the interest rate lower bound in small, open, and euroized economies. The paper introduces a stylized monitoring tool to assess the unintended consequences of low policy rates. The paper is the first attempt to estimate the impact of low interest rate on the public's demand for banknote by denomination. A strong preference for banknotes leads economic agents to require a higher remuneration of banks' deposits, lifting the lower bound above zero. Financial euroization also lifts the lower policy bound due to the higher propensity of substituting domestic with foreign currency-denominated assets as a function of the interest rate differential. Policies aiming at reducing financial euroization contribute to bring down the lower bound.